(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, the great Muhaddith Allama Muhammad Anwarshah Kashmiri’s religious views, in particular, the interdependence of faith and action, the influence of this work of a person who does not act on his faith, as well as his views on the issue of whether action is a part of faith or another, and a brief analysis of the Hanafi-Maturidi belief in this regard information is provided.